Phase transition in magnetic ultra‐thin films - Thao, Pham Huong; Thuan, Ngo Thi; Ny, Phan Thi Han (Hue University Journal of Science: Natural Science, 2019)
In this paper, we study the influence of surface anisotropy on the phase transition in antiferromagnetic and ferromagnetic ultra‐thin films using the functional integral method. Besides, spin fluctuations are also given to illustrate these phase transitions. We find that the phase transition temperature of the ultra‐thin films may be higher or lower than that of the corresponding bulk systems, which depends on the surface anisotropy. Moreover, we also determine crossover points at which the phase transition temperature is not influenced by the thickness of the thin film.